Disrupted actin: a novel player in pathogen attack sensing? - Leontovyčová, Hana; Kalachova, Tetiana; Janda, Martin (The New phytologist, 2020)
The actin cytoskeleton is widely involved in plant immune responses. The majority of studies show that chemical disruption of the actin cytoskeleton increases plant susceptibility to pathogen infection. Similarly, several pathogens have adopted this as a virulence strategy and produce effectors that affect cytoskeleton integrity. Such effectors either exhibit actin-depolymerizing activity themselves or prevent actin polymerization. Is it thus possible for plants to recognize the actin's status and launch a counterattack? Recently we showed that chemical depolymerization of actin filaments can trigger resistance to further infection via the specific activation of salicylic acid (SA) signalling. This is accompanied by several defence-related, but SA-independent, effects (e.g. callose deposition, gene expression), relying on vesicular trafficking and phospholipid metabolism. These data suggest that the role of actin in plant-pathogen interactions is more complex than previously believed. It raises the question of whether plants have evolved a mechanism of sensing pathological actin disruption that eventually triggers defence responses. If so, what is the molecular basis of it? Otherwise, why does actin depolymerization specifically influence SA content but not any other phytohormone? Here we propose an updated model of actin's role in plant-microbe interactions and suggest some future directions of research to be conducted in this area.
Keywords: nemoci rostlin; rostliny; Plants; actin cytoskeleton; plant-microbe interaction; Salicylic Acid; salicylic acid (SA); regulátory růstu rostlin; Plant Diseases; mikrofilamenta; Actins; latrunculin B; Plant Growth Regulators; kyselina salicylová; Actin Cytoskeleton; aktiny; plant immunity